The Effectiveness Application of E-Invoice VAT to The Taxable Entrepreneurs in KPP Pratama Madiun - Nur Wahyuning Sulistyowati; Nik Amah; Farida Styaningrum (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2020)
Value-added tax (VAT) is one of the sources of state revenue from the tax sector. The use of e-invoices is expected to increase taxpayer compliance. This study aims to analyze and test the application of E-Invoice VAT to the compliance of Taxable Entrepreneurs (PKP) listed in KPP Pratama Madiun. This type of research is qualitative research with the explorative method. Data sources are primary data obtained from interviews with Taxable Entrepreneurs (PKP) and Tax Officer. Data analysis use the exploration analysis method. The result of the research shows that: Application of e-invoice within the scope of KPP Pratama Madiun has been effective, Effectiveness of VAT e-invoice implementation improve taxpayer compliance, Several times interviewed states the use of e-invoice is an internet connection problem, and the application of errors sometimes occurs.